2014
DOI: 10.1177/1071100714549190
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Total Ankle Arthroplasty and Ankle Arthrodesis on Uneven Surfaces, Stairs, and Inclines

Abstract: Level II, prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 33 publications
3
37
1
1
Order By: Relevance
“…Similar observations were noted by several other studies examining function and gait of patients after ankle replacement and fusion . In 2015, Jastifer et al stated that while these studies have demonstrated improved gait after both ankle arthroplasty and ankle arthrodesis, neither procedure restores gait to normal. These results prompted us to investigate kinematic mechanisms that may be occurring in adjacent joints and down the kinematic chain which may account for limitations in gait.…”
supporting
confidence: 65%
“…Similar observations were noted by several other studies examining function and gait of patients after ankle replacement and fusion . In 2015, Jastifer et al stated that while these studies have demonstrated improved gait after both ankle arthroplasty and ankle arthrodesis, neither procedure restores gait to normal. These results prompted us to investigate kinematic mechanisms that may be occurring in adjacent joints and down the kinematic chain which may account for limitations in gait.…”
supporting
confidence: 65%
“…Two reported no significant difference between the TAA and AA cohorts [20, 22]. The remaining five studies found that patients performed better on gait analysis after TAA [21, 2325, 29]. Clinical outcomes were collected in six studies [20, 23, 2528].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining five studies found that patients performed better on gait analysis after TAA [21, 2325, 29]. Clinical outcomes were collected in six studies [20, 23, 2528]. Jastifer et al reported improved Beuchel-Pappas scale ( p  = 0.036) and AOFAS ( p  = 0.03) in the TAA cohort over the AA cohort [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Jastifer et al evaluated differences between patients who underwent each procedure in terms of their performance on uneven surfaces, stairs, and inclines 16 . The authors found that, although both groups demonstrated improved postoperative performance at the 1-year follow-up, the patients who had undergone TAA had higher scores walking upstairs, downstairs, and uphill.…”
Section: Total Ankle Arthroplastymentioning
confidence: 99%